THE PROBLEMS OF FRAGMENTATION AND WAYS ITS SETTLEMENT IN INTERNATIONAL AIR LAW - Радзівілл, Олександр Анатолійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: analysis of phenomenon of international law’s fragmentation as one of the aspect its development and codification in different level of delegate jurisdiction given by the example of international air law. Methods of research: general scientific and special methods: historical, comparative-legal, hermeneutical, special-legal – were used in the work. Results: main stages of development and modern levels of the rule-making in international air law and its settlement in context of the problems of fragmentation. Discussion: the ways of settlement of the different level jurisdiction’s rules.